A cell-permeable peptide inhibitor of p55PIK signaling alleviates suture-induced corneal neovascularization and inflammation. Issue 4 (April 2023) - Huang, Jingyi; Zhang, Yiran; Lin, Tao; Yin, Hui; Pan, Yingzhe; Zhu, Meijuan; Zhang, Min
Abstract: To prepare an ophthalmic solution with a cell-permeable TAT peptide (TAT-N24) as the main cell-permeable peptide inhibitor of p55PIK signaling and observe its therapeutic effect on suture-induced corneal neovascularization (CNV) in rats. Sprague-Dawley rats were used to establish a corneal suture (CS) model of CNV. The vehicle and 0.9% TAT-N24 ophthalmic solution was topically administered. CNV induction was assessed on the basis of the clinical performance of each group. Hematoxylin-eosin staining was used to observe pathological changes, and immunohistochemical staining and confocal immunofluorescence were used to determine the localization of factors associated with corneal tissue. The mRNA expression levels of hypoxia-inducible factor (HIF-1α), vascular endothelial growth factor (VEGF-A), nuclear transcription factor κB (NF-κB p65), tumor necrosis factor (TNF-α), interleukin-1β (IL-1β), and interleukin (IL)-6 were determined using real-time quantitative polymerase chain reaction. Western blotting was performed to detect the protein expression levels of HIF-1α and NF-κB p65. TAT-N24 slowed CNV production and reduced the expression of HIF-1α and inflammatory factors in CS models. The mRNA levels of HIF-1α, VEGF-A, NF-kB, TNF-α, IL-1β, and IL-6 significantly decreased. Moreover, the protein levels of HIF-1α and NF-κB p65 were significantly decreased. TAT-N24 can treat CNV and ocular inflammation by inhibiting the HIF-1α/NF-κB signaling pathway in CS. In the early treatment of corneal foreign body trauma, topical application of TAT-N24 can not only reduce the inflammatory response but also inhibit corneal neovascularization.